Point-of-care testing reduces antibiotic prescribing in acute exacerbations of chronic obstructive pulmonary disease: A systematic review and meta-analysis - Xiying Li; Shengyue Qiu; Chaojie Liu; Manzhi Zhao; Xinyi Yang; Haohai Xia; Ruonan Wang; Shanquan Chen; Jie Chen; Jinkun Zheng; Gordon Liu; Shifang Yang; et al. (International Journal of Infectious Diseases)
Background: Challenges in identifying the causes of acute exacerbations of chronic obstructive pulmonary disease (AECOPD) have led to overuse of antibiotics. The advantages of point-of-care testing (POCT) may help to identify pathogens and use antibiotics more appropriately. Methods: We conducted a systematic review to evaluate the effect of POCT to guide antibiotic prescriptions for AECOPD. Adhering to a protocol (CRD42024555847), we searched eligible studies. The outcomes included antibiotic-related and clinical outcomes. We evaluated the risk of bias and performed meta-analyses with subgroup based on the type and testing timing of POCT. Results: A total of 18 studies evaluating 4346 AECOPD patients were included. Overall, POCT significantly reduced the number of AECOPD patients given antibiotic prescriptions by 16% (P < 0.001). Additionally, antibiotic treatment was reduced by 1.19 days (P = 0.04). There was no detrimental impact on clinical outcomes, such as the length of hospital stay (P = 0.19). Our results proved robust to sensitivity analyses. Conclusion: We offered reasonable evidence for using POCT to reduce antibiotic exposure for AECOPD without adversely affecting clinical outcomes. As diagnostic techniques become increasingly important in combating antimicrobial resistance, the use of POCT should be encouraged.